MODEL KEMITRAAN DALAM MANAJEMEN RANTAI PASOKAN UNTUK MENINGKATKAN KEUNGGULAN BERSAING PERUSAHAAN - Sutarmin Sutarmin (JBIMA (Jurnal Bisnis dan Manajemen), 2014)
This study aimed to analyze whether the application of the partnership model of the suppliers in a supply chain system of manufacturing and exporting essential oil can improve the company's competitive advantages. This study is a case study conducted by survey method. The study was conducted at the clove essential oil and derivatives export company in Purwokerto. Departments involved are the Department of Natural Materials Purchasing and Finance Department. Source of data in this research is secondary data and primary data. Secondary data were obtained from the internal data that already exist and are collected by the Department of Natural Materials Purchasing Department and Corporate Finance Department. Primary data was collected through in-depth interviews and focus group discussions (FGD). The results and analysis of research indicate that supplier selection strategy with the partnership model provides financial benefits to the company amounting to 1.565.747.410,63 rupiahs during the period of 6 months. In addition to financial benefits, partnerships also provide increased gain, a harmonious relationship between the company and the vendor, reduce the risk of vertical vendor integration, increasing the acquisition through partnering vendor, the vendor avoids speculation and reduce the risk of adulterants.